Internet Addiction in South Indian Adolescents: Prevalence and YDQ-IAT Diagnostic Agreement - Rock Britto Dharmaraj; George, Neethu; Mahendran, Pavithra; Sarathbabu, Saran; Selvarasu, Sarmila; Rajagopal Vasanthamani, Sanjay Kishora; Abdul Kareem, Salmathul Jaseela; Gunasekaran, Santhosh Kumar; Murugan, Sathiyapriya; Kulothungan, Karthikeyan (National Journal of Community Medicine, 2025)
Background: The Internet has revolutionized global communication while introducing concerning patterns of maladaptive use among adolescents. Internet addiction has emerged as a significant public health concern requiring robust assessment methodologies. This study employs a dual-scale approach to evaluate internet addiction among adolescents, aiming to determine prevalence rates, identify associated risk factors, and assess the concordance between two established assessment instruments. Methodology: A cross-sectional study was conducted among adolescents in the field practicing area of a tertiary care hospital over three months. Two structured assessment tools were employed: Young's diagnostic criteria and Young's Internet Addiction Test, administered through self-completed questionnaires. Demographic data and internet usage patterns were collected alongside addiction assessments. Kappa statistical analysis evaluated concordance between measurement instruments. Results: The study comprised of 1138 participants where 363(31.9%) had internet addiction according to Young`s diagnostic criteria, while Young's Internet Addiction Test classified 696(61.1%) participants with varying addiction levels (385 (33.8%) mild, 239(21%) moderate, 72(6.3%) severe). Male gender, college attendance, and increased daily internet usage were significantly associated with higher addiction rates (p<0.001). Kappa statistics revealed poor agreement (κ=0.185) between the two assessment tools. Conclusion: Male gender, higher age, college attendance, and increased daily internet usage (particularly exceeding five hours) were significantly associated with internet addiction and also slight agreement between assessment tools were found.